2022
DOI: 10.30935/scimath/11661
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Preschool Teachers’ Epistemological Beliefs on Content-Based Pedagogical Conceptualizations and PCK Integrations towards Science Teaching

Abstract: This exploratory case study aims to determine how preschool teachers' epistemological beliefs influence their pedagogical conceptualizations of science teaching. The research was conducted with a total of 10 teachers that were selected among 61 preschool teachers by their epistemological beliefs. The participants were divided into two sub-groups consisting of five persons each to represent the lower and higher epistemological profiles, based on their scores obtained from the Epistemological Belief Scale Toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…In the interviews, participants shared their experiences to support their views about pursuing use of ICTs for teaching science. One participant whose views indicated low CK (Kutluca & Mercan, 2022) and TCK for integration of ICT by admitting that in some instances in class s/he did not know how to pose useful questions to students said: "I will love to use ICTs. For example, when I was doing my practical teaching, we had everything.…”
Section: Participants' Views About Pursuing the Use Of Icts For Teach...mentioning
confidence: 99%
“…In the interviews, participants shared their experiences to support their views about pursuing use of ICTs for teaching science. One participant whose views indicated low CK (Kutluca & Mercan, 2022) and TCK for integration of ICT by admitting that in some instances in class s/he did not know how to pose useful questions to students said: "I will love to use ICTs. For example, when I was doing my practical teaching, we had everything.…”
Section: Participants' Views About Pursuing the Use Of Icts For Teach...mentioning
confidence: 99%
“…Moreover, a robust correlation has been established between beliefs and their practical manifestations, particularly within educational contexts. Epistemological beliefs, constituting a foundational framework of assumptions regarding knowledge, represent an intricate and self-contained network of beliefs that can be nurtured (Kutluca & Mercan, 2022). It is crucial to note the complexity inherent in understanding beliefs (Sari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also indicated that the teachers' PCKs have a much more complex structure from this perspective. Because of this reason, scholars (Gess-Newsome & Lederman, 1999;Kutluca & Mercan, 2022;Loughran et al, 2001) have suggested that more than a single method ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/…”
Section: Introductionmentioning
confidence: 99%